Cladobranchia (Gastropoda, Nudibranchia) as a Promising Model to Understand the Molecular Evolution of Photosymbiosis in Animals - Rola, Marcellina; Frankenbach, Silja; Bleidissel, Sabrina; Sickinger, Corinna; Donath, Alexander; Frommlet, Jörg C.; Greve, Carola; Serôdio, João; Preisfeld, Angelika; Melo Clavijo, Jenny; Christa, Gregor (Frontiers in Marine Science, 2022)
Symbiosis with photoautotrophic organisms has evolved in various species and even whole animal lineages, which allowed them to directly benefit from photosynthesis. This so-called photosymbiosis is best studied in cnidarians, which primarily establish symbioses with dinoflagellates from the family Symbiodiniaceae. In most other animals the mechanisms of establishing photosymbiosis, the physiological basis, and the evolution of a photosymbiotic life history remain poorly understood. Sea slugs belonging to the Cladobranchia (Gastropoda, Nudibranchia) are no exception, and are a rather neglected animal lineage in the research field of photosymbiosis. Yet, studying these sea slugs holds great potential to establish a unique photosymbiosis model, as they are the only known taxon that has evolved two different strategies to acquire their symbiont: either from cnidarian prey (thus becoming a secondary host) or directly out of the water column. The mechanisms for photobiont uptake and maintenance are unknown for these sea slugs, but might be similar to those of cnidarians. However, in terms of the evolution of photosymbiosis, Cladobranchia seem to share many commonalities with more closely related sea slugs belonging to the Sacoglossa, which only maintain the chloroplasts of the algae they feed on. Hence, Cladobranchia have the potential to shed light on the evolution of photosymbiosis in taxonomically divergent animals that also harbor photobionts of different evolutionary lineages.